Full thermal experimental assessment of a dendritic turbine vane cooling scheme - Luque, S; Batstone, J; Gillespie, D; Povey, T; Romero, E (American Society of Mechanical Engineers, 2013)
A full thermal experimental assessment of a novel dendritic cooling scheme for highpressure turbine vanes has been conducted and is presented in this paper, including a comparison to the current state-of-the-art cooling arrangement for these components. The dendritic cooling system consists of cooling holes with multiple internal branches that enhance internal heat transfer and reduce the blowing ratio at hole exit. Three sets of measurements are presented, which describe, first, the local internal heat transfer coefficient of these structures and, secondly, the cooling flow capacity requirements and overall cooling effectiveness of a highly engine-representative dendritic geometry. Fullcoverage surface maps of overall cooling effectiveness were acquired for both dendritic and baseline vanes in the Annular Sector Heat Transfer Facility, where scaled nearengine conditions of Mach number, Reynolds number, inlet turbulence intensity, and coolant-to-mainstream pressure ratio (or momentum flux ratio) are achieved. Engine hardware was used, with laser-sintered metal counterparts for the novel cooling geometry (their detailed configuration, design, and manufacture are discussed). The dendritic system will be shown to offer improved overall cooling effectiveness at a reduced cooling mass flow rate due to a more uniform film cooling effectiveness, a decreased tendency for films to lift off in regions of low external cross flow, improved through-wall heat transfer and internal cooling efficiency, increased internal wetted surface area of the cooling holes, and the enhanced turbulence induced in them.